Selectivity oxidation of benzyl alcohol using mesoporous g-C3N4 catalysts prepared by hard template method - Ramesh, Arumugam; Da, Chau Thi; Manigandan, R.; Bhargav, Pamula Balaji; Nguyen-Le, Minh-Tri (Colloid and interface science communications, 2022)
The mesoporous g-C3N4 catalyst was prepared by a hard template method using melamine (C and N source) and Santa barbara amorphous-16 (SBA-16) (silica source). The prepared catalysts were characterized by various techniques such as X-ray Diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), Thermogravimetric analysis (TGA), N2-sorption study, Scanning electron microscope (SEM), and Transmission Electron Microscopy (TEM). The selective oxidation of benzyl alcohol (BzOH) to benzaldehyde (BzH) was performed using SBA-16, bulk (B) and mesoporous (M) (g-C3N4). The g-C3N4-(M) catalyst exhibited superior catalytic performance of 97% and BzH selectivity of 95% under optimized reaction conditions (100 °C, Tertbutylhydroperoxide (TBHP) 1 ratio, 2.5 h, and 0.1 g of catalysts). The reusability of the g-C3N4-(M) catalyst was examined up to the sixth cycle, and it revealed that the prepared g-C3N4-(M) catalyst is highly stable, which is associated with the physicochemical properties of catalyst. [Display omitted] •Synthesis of mesoporous g-C3N4 catalysts by hard template method•Selective oxidation of benzyl alcohol to benzaldehyde at 100 °C in the aqueous phase batch reactor•Mesoporous g-C3N4 catalyst was found the superior catalyst for benzaldehyde production.